Utilization of glycerol during consecutive cycles of Lactobacillus reuteri fermentation under pressure: The impact on cell growth and fermentation profile. (December 2018) - Mota, Maria J.; Lopes, Rita P.; Sousa, Sérgio; Gomes, Ana M.; Lorenzo, Jose M.; Barba, Francisco J.; Delgadillo, Ivonne; Saraiva, Jorge A.
Graphical abstract: Highlights: Fermentation cycles at high pressure affected cell growth and fermentation profile. The highest 1, 3-PDO titers, yields and productivities were achieved at 10 MPa. At 25 MPa, the 1, 3-PDO increment was less pronounced and highly variable. The fermentation cycles under pressure promoted shifts in by-product formation. At 10 MPa, metabolic selectivity was shifted towards the production of 1, 3-PDO. Abstract: Exposure of bacterial cells to sub-lethal high pressure (HP) during growth and fermentation may promote development of new adaptive features, with potential biotechnological interest. The present work evaluated the effect of consecutive fermentation cycles under HP on Lactobacillus reuteri growth and glycerol/glucose co-fermentation. At all conditions tested (0.1, 10 and 25 MPa), 1, 3-propanediol production from glycerol was enhanced over the cycles. The highest titers, yields and productivities were achieved at 10 MPa. In addition, the HP-cycles promoted shifts in by-product formation (ethanol, acetate and lactate), with different profiles according to the pressure. Ratios between 1, 3-propanediol:by-products increased throughout the cycles, especially at 10 MPa, indicating shifts in metabolic selectivity. Data regarding the effects of HP-cycles on protein and nucleic acid leakage suggested that, in some cases, L. reuteri changed membrane permeability as a possible adaptation to HP. Overall, this work confirms that HP may be an useful tool to stimulate production of 1, 3-propanediol, as well as other biocompounds.